Analisis Implikatur Dalam Konten Youtube Podkaesang Depan Pintu (PDP) Serta Penyusunannya Sebagai Bahan Ajar Teks Anekdot Kelas X Jenjang SMK - Putri, Rizkia; Hartati, Dian; Adham, M. Januar Ibnu (Peneliti.net, 2024)
Critical thinking skills in teenagers can be trained in learning Indonesian with anecdotal text material. In an anecdote text, there is an implied meaning that the author wants to convey. To be able to find out the implied meaning, an implicature analysis is needed. A statement that contains implicatures can be found anywhere, such as in the YouTube content Podkaesang Depan Pintu (PDP). The Podkaesang Depan Pintu (PDP) content attracts the public's attention because it contains a lot of discussion about politics, but also contains elements of comedy. Therefore, this research aims to (1) describe the types of implicatures in Podkaesang Depan Pintu (PDP) Youtube content (2) describe the function of implicatures used in Podkaesang Tepi Pintu (PDP) Youtube content (3) describe the preparation of research results for teaching materials (E-Module) anecdotal text material for class This research uses a qualitative approach with an analytical description method. The technique used in research is listening and taking notes. The results of the research show that in six episodes of Podkaesang Depan Pintu (PDP) content, 18 implicatures were found, consisting of 10 conventional implicatures and 8 conversational implicatures. The implicature functions found were 18 data consisting of the assertive functions 'state', 'express opinions' and 'complain'. As for the expressive function, there are 'to criticize', 'criticize', 'criticize' and 'praise'. The dominant function that appears is the assertive function of 'declaring'. Apart from that, the results of this research were also used to prepare teaching materials in the form of E-Modules for anecdotal text material for class